A banana transcriptional repressor MaAP2a participates in fruit starch degradation during postharvest ripening - Xiao, Yunyi; Li, Ying; Ouyang, Lejun; Yin, Aiguo; Xu, Bo; Zhang, Ling; Chen, Jianye; Liu, Jinfeng (Frontiers in Plant Science, 2022)
Fruit postharvest ripening is a crucial course for many fruits with significant conversion of biosubstance, which forms an intricate regulatory network. Ethylene facilitates the ripening process in banana with a remarkable change of fruit starch, but the mechanism adjusting the expression of starch degradation-related enzyme genes is incompletely discovered. Here, we describe a banana APETALA2 transcription factor (MaAP2a) identified as a transcriptional repressor with its powerful transcriptional inhibitory activity. The transcriptional level of MaAP2a gradually decreased with the transition of banana fruit ripening, suggesting a passive role of MaAP2a in banana fruit ripening. Moreover, MaAP2a is a classic nucleoprotein and encompasses transcriptional repressor domain (EAR, LxLxLx). More specifically, protein–DNA interaction assays found that MaAP2a repressed the expression of 15 starch degradation-related genes comprising MaGWD1, MaPWD1, MaSEX4, MaLSF1, MaBAM1-MaBAM3, MaAMY2B/2C/3A/3C, MaMEX1/2, and MapGlcT2-1/2-2 via binding to the GCC-box or AT-rich motif of their promoters. Overall, these results reveal an original MaAP2a-mediated negative regulatory network involved in banana postharvest starch breakdown, which advances our cognition on banana fruit ripening and offers additional reference values for banana varietal improvement.